Mapping adolescent sexual and reproductive health research in sub-Saharan Africa: protocol for a scoping review. Issue 7 (1st July 2020) - Ajayi, Anthony Idowu; Ushie, Boniface Ayanbekongshie; Mwoka, Meggie; Igonya, Emmy Kageha; Ouedraogo, Ramatou; Juma, Kenneth; Aboderin, Isabella
Abstract : Introduction: Previous studies have attempted to review the vast body of evidence on adolescent sexual and reproductive health (ASRH), but none has focused on a complete mapping and synthesis of the body of inquiry and evidence on ASRH in sub-Saharan Africa (SSA). Such a comprehensive scoping is needed, however, to offer direction to policy, programming and future research. We aim to undertake a scoping review of studies on ASRH in SSA to capture the landscape of extant research and findings and identify gaps for future research. Methods and analysis: This protocol is designed using the framework for scoping reviews developed by the Joanna Briggs Institute. We will include English and French language peer-reviewed publications and grey literature on ASRH (aged 10–19) in SSA published between January 2010 and June 2019. A three-step search strategy involving an initial search of three databases to refine the keywords, a full search of all databases and screening of references of previous review studies for relevant articles missing from our full search will be employed. We will search AJOL, JSTOR, HINARI, Scopus, Science Direct, Google Scholar and the websites for the WHO, UNICEF, UNFPA, UNESCO and Guttmacher Institute. Two reviewers will screen the titles, abstracts and full texts of publications for eligibility and inclusion—using Covidence (an online software). We will then extract relevant information from studies that meet the inclusion criteria using a tailored extraction frame and template. Extracted data will be analysed using descriptive statistics and thematic analysis. Results will be presented using tables and charts and summaries of key themes arising from available research findings. Ethics and dissemination: Ethical approval is not required for a scoping review as it synthesises publicly available publications. Dissemination will be through publication in a peer-review journal and presentation at relevant conferences and convening of policymakers and civil society organisations working on ASRH in SSA.